Prevalencia de lesiones músculo esqueléticas en región cervical de los estudiantes de odontología: un estudio comparativo entre los debutantes y los estudiantes de fin de carrera - Flores Hernández, Clara Inés (2017)
Musculoskeletal disorders are a frequent problem that dentists find either in static posture for prolonged times or repetitive movements. The most affected regions are: back, neck, shoulder, wrist and hand. Gender must also be taken into account, since young women are more likely to acquire these lesions according to a study conducted at the University of Dentistry Barcelona (Harutunian et al., 2011). Objective: To determine the number of dentistry students with musculoskeletal lesions in the cervical region. Materials and Methods: Sixty dental students, both sexes between the ages of 18 and 28 participated in this study, 30 were from Clinic 1 (first semester of practices) and 30 from Clinic 5 (last semester of practices). The sample was submitted to an assessment of the pain threshold using algometry, joint ranges with inclinometry and the Nordic Questionnaire to determine functional disability in the cervical region. Results: The results showed that the muscles subjected to algometry showed a significant interaction, comparing the two groups of the sample, that is, the sternocleidomastoid, upper trapezius, infraspinatus, and rounder muscles were more affected in the students Of Clinic 5. Conclusion: After the evaluations carried out in this study, we conclude that Clinical 5 students have more musculoskeletal disorders at the cervical level than Clinic 1 students. Key Words: Musculoskeletal disorders, dentists, cervical, neck, algometry, inclinometry.